Stagnasi Pembelajaran Al-Qur’an di Sekolah: Kritik atas Bahan Ajar PAI SD, SMP, dan SMA - Ju`subaidi Ju`subaidi; Anwar Mujahidin (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2022)
The development of PAI teaching materials on Qur'anic sub-materials is related to the development of Qur'anic science and tafsir. If the development of teaching materials for the Qur'an does not pay attention to the trend of Qur'anic studies, the understanding obtained by students is less relevant to the context of life they experience. This article will discuss three fundamental things: how is the structure of Qur'anic material in PAI subjects in schools, how is the contextuality of Qur'anic understanding presented in PAI teaching materials in schools, and how is the approach needed for the development of Qur'anic material in PAI teaching materials in schools. The research method used is library research with data collected through documentation method in the form of Islamic teaching materials for elementary, junior and senior high schools published by the Centre for Curriculum and Bookkeeping of the Ministry of National Education. The collected data were then classified, presented in the presentation of data and analysed by the method of text analysis with an explanatory analysis approach, namely describing and criticising the substance of its content according to the categories in the research problem. The results of the study show a discrepancy between the objectives of learning al-Qu'ran at the elementary, junior high and high school levels with a number of supporting things. The priority of learning to read as the purpose of learning the Qur'an at the primary level is disrupted by the purpose of learning the Qur'an at the primary level which is also aimed at understanding the content of the Qur'an by interpreting the verses of the Qur'an. While the material for understanding the content of the Qur'an at the junior and senior high school levels is still very minimal from the source of tafsir sources so that the learning material is less contextual and actual.